Dubai international financial centre courts as an example of excellence and international acceptance - Hwang, Michael (Право и государство, 2015)
In article is carried out the short review of the Dubai international financial center. In particular, some factors of successful activity of the Courts of this center is revealed. Among them are mentioned such moments as doing legal case exclusively in English, choosing of Anglo- Saxon model of legal proceedings, recruitingexperienced judges, creating comfortable conditions for foreign business.
Keywords: the United Arab Emirates; the Emirate of Dubai; the Government of Dubai; Dubai law; court; international business; financial law; legal proceedings; Research Subject Categories::LAW/JURISPRUDENCE